Promoting mental health for optimal performance in sports - Alexander Schorb; Ulf Häfelinger; Marek Pesicka; Simon Kohl; Felix Karus; Andreas Kaiser; Günter Schiepek; Wolfgang Aichhorn (Sports Psychiatry)
Abstract: Introduction: Mental symptoms and disorders in competitive sports can reduce performance and may occur as sport-specific and non-specific disorders. Unrecognized or inadequately treated mental health symptoms and disorders in athletes can have serious health consequences. Methods: A review of the medical literature identified relevant publications on the topics of sports psychiatry and mental health in competitive athletes. A corresponding health concept was developed in this context. Results: The promotion of mental health is not yet an integral part of the care structures in competitive sports. Competitive success founds social status of athletes and contributes significantly to their self-esteem. In the case of participation loss or injury, the implicit or explicit pressure to restore function and performance quickly poses a particular challenge. Treatments under these conditions can differ from psychotherapeutic processes as usual. Apart from that, restoring health alone is not enough for athletes. The restoration of performance appears to be a decisive factor. The possibility of performance enhancement within the framework of care concepts is an attractive form of support for athletes. Conclusion: Performance serves to promote mental health and vice versa. The promotion of performance represents a fundamental shift in the paradigm of mental health care in sports. Promoting performance in the context of mental health care could help to ensure that more of the hard-to-reach group of elite athletes can be involved and, if necessary, receive early and professional treatment. Furthermore, a reduction in the stigmatization of mental disorders in sports could also be expected.